How do the institutions matter for MNE subsidiaries' CSR in host countries? Evidence from Chinese overseas subsidiaries - Jeoung Yul Lee; Jiyul Choi; Simon Shufeng Xiao; Yong Kyu Lew; Byung Il Park (BRQ Business Research Quarterly, 2024)
Based on the institutional perspective, this article examines whether institutional pressures in home and host countries affect multinational enterprise (MNE) subsidiaries' corporate social responsibility (CSR) practices and whether the institutional distance between home and host countries moderates these relationships. We collect data from 185 Chinese MNEs' 349 foreign subsidiaries operating in 27 host countries and conduct a cross-classified multilevel model analysis of the data. The findings indicate that institutional pressures in home and host countries significantly affect the CSR practices of the MNE subsidiaries operating in host countries. Also, we find that the formal and informal institutional distances between the home and host countries exert different interaction effects on these CSR practices. The findings from this study offer useful implications for MNEs' social strategies for sustainability.
Keywords: G38; L16; M16; Q17; 650; Corporate social responsibility; institutions; institutional distance; multinational enterprise; China